Anti-Tumor Mechanisms Associated With Regulation of Non-Coding RNA by Active Ingredients of Chinese Medicine: A Review - Liu, Tian-Jia; Hu, Shuang; Qiu, Zhi-Dong; Liu, Da (Frontiers in Oncology, 2021)
Cancer has become the second leading cause of death worldwide; however, its complex pathogenesis remains largely unclear. Previous research has shown that cancer development and progression are closely associated with various non-coding RNAs, including long non-coding RNAs and microRNAs, which regulate gene expression. Target gene abnormalities are regulated and engaged in the complex mechanism underlying tumor formation, thereby controlling apoptosis, invasion, and migration of tumor cells and providing potentially effective targets for the treatment of malignant tumors. Chemotherapy is a commonly used therapeutic strategy for cancer; however, its effectiveness is limited by general toxicity and tumor cell drug resistance. Therefore, increasing attention has been paid to developing new cancer treatment modalities using traditional Chinese medicines, which exert regulatory effects on multiple components, targets, and pathways. Several active ingredients in Chinese medicine, including ginsenoside, baicalin, and matrine have been found to regulate ncRNA expression levels, thus, exerting anti-tumor effects. This review summarizes the scientific progress made regarding the anti-tumor mechanisms elicited by various active ingredients of Chinese medicine in regulating non-coding RNAs, to provide a theoretical foundation for treating tumors using traditional Chinese medicine.